Ariconium, Herefordshire : An Iron Age settlement and Romano-British 'small town' (2013)
The Roman 'small town' of Ariconium in southern Herefordshire has long been known as an important iron production center but has remained very poorly understood. The town is suggested to have developed from a late Iron Age Dobunnic tribal center, which owed its evident status and wide range of contacts to control of the production and distribution of Forest of Dean iron. Rapid expansion during the second half of the 1st century AD indicates that the local population was able to articulate rapidly with the economic opportunities the Roman conquest brought. The town developed as a typical small roadside settlement and a major iron production center but a heavy reliance on iron working appears to have made it especially vulnerable to the economic decline of the latter part of the 4th century.